Perilesional edema diameter associated with brain metastases as a predictive factor of response to radiotherapy in non-small cell lung cancer - Arrieta, Oscar; Bolaño-Guerra, Laura Margarita; Caballé-Pérez, Enrique; Lara-Mejía, Luis; Turcott, Jenny G.; Gutiérrez, Salvador; Lozano-Ruiz, Francisco; Cabrera-Miranda, Luis; Arroyave-Ramírez, Andrés Mauricio; Maldonado-Magos, Federico; Corrales, Luis; Martín, Claudio; et al. (Frontiers in Oncology, 2023)
Background: Different prognostic scales exist in patients with brain metastasis, particularly in lung cancer. The Graded Prognostic Assessment for lung cancer using molecular markers (Lung-molGPA index) for brain metastases is a powerful prognostic tool that effectively identifies patients at different risks. However, these scales do not include perilesional edema diameter (PED) associated with brain metastasis. Current evidence suggests that PED might compromise the delivery and efficacy of radiotherapy to treat BM. This study explored the association between radiotherapy efficacy, PED extent, and gross tumor diameter (GTD). Aim: to evaluate the intracranial response (iORR), intracranial progression-free survival (iPFS), and overall survival (OS) according to the extent of PED and GT. Methods: Out of one hundred and fourteen patients with BM at baseline or throughout the disease, sixty-five were eligible for the response assessment. The GTD and PED sum were measured at BM diagnosis and after radiotherapy treatment. According to a receiver operating characteristic (ROC) curve analysis, cut-off values were set at 27 mm and 17 mm for PED and GT, respectively. Results: Minor PED was independently associated with a better iORR [78.8% vs. 50%, OR 3.71 (95% CI 1.26-10.99); p = 0.018] to brain radiotherapy. Median iPFS was significantly shorter in patients with major PED [6.9 vs. 11.8 months, HR 2.9 (95% CI 1.7-4.4); p < 0.001] independently of other prognostic variables like the Lung-molGPA and GTD. A major PED also negatively impacted the median OS [18.4 vs. 7.9 months, HR 2.1 (95% CI 1.4 -3.3); p = 0.001]. Conclusion: Higher PED was associated with an increased risk of intracranial progression and a lesser probability of responding to brain radiotherapy in patients with metastatic lung cancer. We encourage prospective studies to confirm our findings.